Food industry biowaste as substrate for biosolvents production focusing on lactic acid and ethyl lactate - Mai, Sofia; Barambouti, Elli Maria; Karamplia, Varvara; Stavraki, Chrysanthi; Loizidou, Maria (Technical Annals, 2023)
Solvents represent a major category of chemicals due to their necessity in a variety of industries. The majority of solvents derived from fossil carbon are hazardous to both human health and the environment. In this context, it seems imperative to convert biomass into new alternative greener solvents. The present study concentrates on the production of two biosolvents; namely lactic acid and ethyl lactate, from biowaste of baby food industry. For the production of lactic acid parameters as the dosages of enzymes (5 mg/gLactose and 20 mg/gLactose) and inoculum size (5% v/v and 10% v/v) were examined. The lactic acid concentration reached almost 17.3g/L after 144 hours with 5mgLactozymePure/glactose and 10%v/v inoculum size. Repeated fermentation was also applied yielding a lactic acid productivity of 0.97 g/L h, which is 8 times higher than the conventional batch fermentation. Moreover, the production of ethyl lactate from bioethanol and lactic acid from the fermentation broth was examined. Lactic acid conversion yields as high as 59.9% at 255min were observed. Overall, the results of this work are very promising but further research is needed to optimize conditions and evaluate scalability of the production of these biosolvents from biowaste, since the production of lactic acid and ethyl-lactate from biowaste provides a sustainable approach to the circular economy, limiting waste and minimizing the environmental effect of industrial processes.